Determination of the best reservoir units for Upper Shale Member of the Zubair Formation by using several petrophysical properties, Southern Iraq - Lathi A Mahdi1, Maher M Mahdi2, Amna M Handhal3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Zubair Formation is considered the main hydrocarbon reservoir in the center and the south of Iraq’ oilfields. The formation has five members, namely, Upper Shale, Upper sand, Middle Shale, Lower sand and Lower shale Members. This work concentrates on the Upper Shale Member of the Zubair Formation in the X-field in the south area of Iraq. Three wells (A, B, and C) were chosen to evaluate the petrophysical properties of the Upper Shale Member in the study area using the Geolog software. The analysis of the conventional well log behaviors (gamma-ray, sonic and resistivity logs) proved that this member can be subdivided into three reservoir units separated by shale beds. The thickness of the member in the study area ranges between 95-100 m. The petrophysical properties were calculated for the reservoir units. In all wells, reservoir unit 2 shows the best petrophysical properties. However, the best reservoir characteristics were found in the well B.